Digital Promotion Strategy for Affiliate Shaquila Syifa Viandra on The Tiktok Account @Shaaaqy In 2025 - Anisa Ambar Jati; Haryadi Arief Nuur Rasyid (Jogjakarta Communication Conference (JCC), 2026)
This study examines how Shaquila Syifa Viandra promotes affiliate-based products through her TikTok account @shaaaqy. The presence of affiliate features encourages performance-based promotional practices that are highly dependent on content creativity and audience trust levels.  The purpose of this study is to describe the process of planning, implementing, and evaluating affiliate promotion strategies in short video formats. The research uses a descriptive qualitative approach with interview techniques and content documentation analysis during the period of May–July 2025. The analytical frameworks used are SOSTAC and AISAS. The findings show that understanding the characteristics of the platform, utilizing storytelling based on personal experiences, consistency in publication, and evaluation through content performance data are key factors in the success of promotion. Affiliate performance on TikTok is reflected in engagement levels, audience trust, and sales conversions.